2009
DOI: 10.1002/chem.200901799
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Affinity towards a Bacterial Lectin through Multivalent Topological Isomers of Calix[4]arene Glycoconjugates

Abstract: A family of seven topologically isomeric calix[4]arene glycoconjugates was prepared through the synthesis of a series of alkyne-derivatised calix[4]arene precursors that are suitable for the attachment of sugar moieties by microwave-assisted copper(I)-catalysed azide-alkyne cycloaddition (CuAAC). The glycoconjugates thus synthesised comprised one mono-functionalised derivative, two 1,2- or 1,3-divalent regioisomers, one trivalent and three tetravalent topoisomers in the cone, partial cone or 1,3-alternate conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 58 publications
7
168
0
Order By: Relevance
“…Considering the multivalency of lectins, the synthesis of multivalent ligands is a classical way for gaining avidity. Indeed, the first tetravalent galactose-containing ligand for PA-IL demonstrated a 850-fold increase in affinity compared with the monomeric ligand (57). Combining the detailed knowledge about the structure and energetics of the binding site together with the multivalency approach will be the route for the design of drugs active against P. aeruginosa infection.…”
Section: Acceptormentioning
confidence: 99%
“…Considering the multivalency of lectins, the synthesis of multivalent ligands is a classical way for gaining avidity. Indeed, the first tetravalent galactose-containing ligand for PA-IL demonstrated a 850-fold increase in affinity compared with the monomeric ligand (57). Combining the detailed knowledge about the structure and energetics of the binding site together with the multivalency approach will be the route for the design of drugs active against P. aeruginosa infection.…”
Section: Acceptormentioning
confidence: 99%
“…Recently, interest has focused on the use of calixarene derivatives in biological systems be it as drugs, drug delivery systems, or imaging agents. In the design of drug molecules, particular attention has been paid to calixarenes as antimicrobials (6)(7)(8), as vaccines (9) and as anticancer agents (10). In the field of drug delivery, agents for nucleic acids based on single calixarenes (11)(12)(13) have shown promise and we have recently shown that larger arrays of cationic calix [4]arene, so-called multicalixarenes, are able to transfect DNA effectively (14).…”
mentioning
confidence: 99%
“…There is a relation between Ca +2 ion concentrations and glycoconjugates in the cell. It has been published that Ca +2 ions have importance roles in both; the secretion of glycoconjugates from the cells, and the binding of lectin to glycan moieties of glycoconjugates (cell-cell adhesion and cell-environment adhesion) 34 . Thus, Ca…”
Section: Resultsmentioning
confidence: 99%
“…They were free of diabetes mellitus, hypertension, cardiovascular, and immune diseases and they have received no medications (by history taking) .There age was ranged between (20-50) years. They were classified according to the number of cigarette sticks smoked per day and the duration of smoking, into; heavy smokers (31) who used to smoke (≥20) sticks per day for ≥ 10 years, moderate smokers (26) used to smoke (10-19) sticks per day for (4-7) years, passive smokers (30) who are non-smokers, but living with smokers 23 , and finally non-smokers (control) (34) who are non-smokers and living with non-smokers. About (10) ml of blood was withdrawn from each volunteer, and then it was collected in a container with no anticoagulant.…”
Section: Subjects and Samples Collectionmentioning
confidence: 99%